A novel nitroethylene-based porphyrin as a NIR fluorescence turn-on probe for biothiols based on the Michael addition reaction. (January 2018) - Wang, Qing; Ma, Fangtao; Tang, Weiqiang; Zhao, Shuangliang; Li, Chengjie; Xie, Yongshu
Abstract: Biothiols, such as cysteine (Cys), homocysteine (Hcy), and glutathione (GSH), play essential roles in many physiological and pathological processes. In this work, three porphyrin derivatives, XQ1, XQ2 andXQ3, were synthesized by combining the porphyrin framework with nitroethylene, bis(methoxycarbonyl)ethylene and dicyanoethylene moieties, respectively.XQ1 was almost nonfluorescent, which could be utilized as a good starting point for developing fluorescence turn-on probes. Thus, XQ1 exhibits fast fluorescence enhancement and high selectivity towards the biothiols based on the Michael addition mechanism. It also exhibits high sensitivity towards the biothiols with the detection limits of 0.65–1.1 μM. In addition, XQ1 was successfully applied to cell imaging in living A549 cells for visualizing the biothiols. The results compose a good example of designing porphyrin derivatives for detecting biothiols, with the advantages of dramatic fluorescence enhancement in the NIR wavelength range, which exhibits good cell membrane permeability and practicability in detecting both exogenous and endogenous biothiols. Graphical abstract: A novel nitroethylene-based porphyrin was synthesized and used as a NIR fluorescent probe for biothiols based on the Michael addition reaction. Highlights: A novel NIR fluorescence turn-on probe for biothiols based on the Michael addition reaction. Nitroethylene group successfully introduced to a porphyrin platform for quenching its fluorescence. An excellent porphyrin-based biothiol probe with good biocompatibility and long-wavelength emission.